ANALISIS MATERI MENYIBAK ILMU DALAM LAPORAN HASIL OBSERVASI DENGAN KURIKULUM BUKU TEKS - Rosmawaty Harahap; Sofia Ayu Wandan; Theresa Intan S; Tiory Sitanggang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the suitability of the "Uncovering Knowledge in Observation Reports" material with the applicable curriculum in textbooks. The background of this research is based on the importance of alignment between learning materials in textbooks and curriculum requirements so that learning objectives can be achieved optimally and systematically. Textbooks, as one of the primary learning resources, play a crucial role in supporting the classroom learning process. Therefore, the suitability of the material content with the competencies expected in the curriculum requires in-depth study. The method used in this study was a descriptive qualitative method with a literature study approach. Data were obtained through content analysis of the material in textbooks and relevant curriculum documents, such as core competencies and basic competencies. Data analysis techniques were carried out by identifying, classifying, and comparing the material's suitability with curriculum standards. The results showed that the material was generally in line with the curriculum, both in terms of objectives, structure, and learning activities. However, there were still some shortcomings in the depth of the material and the variety of exercises. Thus, further development is needed to make learning more effective.